Knowledge and Practice on Breastfeeding among Mothers of Infant - Adhikari, Tulashi; Subedi, Ishwar (Journal of Food Science and Technology Nepal, 2014)
This descriptive explorative study was carried out with the aim of finding out the current status on breastfeeding among mothers of infants in Kanti Children Hospital, Maharajgunj, Kathmandu. A total of 100 mothers attending maternal and child health (MCH) Clinic of Kanti Children’s hospital were selected on the first come first basis. A semi- structured questionnaire was used to collect data that assess the knowledge and actual practices of mothers regarding breastfeeding. The study finding revealed that 52% responded has correct meaning of exclusive breastfeeding. Regarding the initiation of breastfeeding only 41% respondents fed their babies correctly within 1 hour. Twenty six percent of them had given Prelacteal feeding from 52.6% of mothers from rural and 20.8% mothers from urban area. Only 12% of respondents had knowledge about expressing breast milk (EBM) and among them only 8.3% practiced it. Regarding the duration of exclusive breastfeeding (EBF), 34% respondents had given EBF up to 6 months, 26% had given prelacteal feed and 26% respondents did not practice EBF from 1st day of life. DOI: http://dx.doi.org/10.3126/jfstn.v8i0.11754 J. Food Sci. Technol. Nepal, Vol. 8 (71-74), 2013